Tailored multivalent targeting of siglecs with photosensitizing liposome nanocarriers - Almeida Marrero, Verónica (2022)
The modification of surfaces with multiple ligands allows the formation of platforms for the study of multivalency in diverse processes. Herein we use this approach for the implementation of a photosensitizer (PS)-nanocarrier system that binds efficiently to siglec-10, a member of the CD33 family of siglecs (sialic acid (SA)-binding immunoglobulin-like lectins). In particular, a zinc phthalocyanine derivative bearing three SA moieties (PcSA) has been incorporated in the membrane of small unilamellar vesicles (SUVs), retaining its photophysical properties upon insertion into the SUV's membrane. The interaction of these biohybrid systems with human siglec-10-displaying supported lipid bilayers (SLBs) has shown the occurrence of weakly multivalent, superselective interactions between vesicle and SLB. The SLB therefore acts as an excellent cell membrane mimic, while the binding with PS-loaded SUVs shows the potential for targeting siglec-expressing cells with photosensitizing nanocarriers.